Penegakan Hukum Pidana di Bidang Perikanan (Berdasarkan Undang-Undang Nomor 45 Tahun 2009 Tentang Perubahan Atas Undang-Undang Nomor 31 Tahun 2004 Tentang Perikanan) - Jeanne Darc Noviayanti Manik (Perspektif Hukum, 2018)
The government must play a role in protecting the development of the fisheries natural resource industry, so that Indonesian fishermen must have the potential for independence in the management of the fishing industry. The wealth of Indonesia's natural resources, especially in the field of fisheries, allows the emergence of various crimes in the territory of Indonesia, for example illegal fishing, foreign fishermen enter Indonesian territory without legal documents and so on. This research is a legal research. The research was conducted to find the principle of law, which regulates binding legal norms in general and formed or stipulated by authorized institutions or officials through the procedures stipulated in the legislation, especially those relating to the norms governing criminal law policy in the field of fisheries in sovereignty country. Criminal arrangements generally provide therapy as well as a deterrent effect on the perpetrators of crime, including the perpetrators of fisheries. With the existence of criminal threats that have been stipulated by the provisions of the law, it is expected to reduce or reduce the perpetrators of fisheries criminal offenses.